Biodegradation of low density polyethylene (LDPE) modified with dye sensitized titania and starch blend using Stenotrophomonas pavanii. (September 2016) - Mehmood, Ch. Tahir; Qazi, Ishtiaq A.; Hashmi, Imran; Bhargava, Samarth; Deepa, Sriramulu
Abstract: Plastic goods including plastic shopping bags, which are generally made from low density polyethylene (LDPE), are a cause of considerable environmental nuisance. Development of a material that would degrade, due to simple factors i.e. sunlight and/or biotic factors, in the open environment, is therefore, of considerable interest. Biodegradation of photodegraded and non-photodegraded LDPE films, modified with food grade dye sensitized titania (TiO2 ) nanoparticles and starch blend, was evaluated under laboratory conditions. Bacterial strains were isolated from solid waste dump site using enrichment culture and two step screening procedure for their ability to degrade LDPE. Bacterial strains capable of growing in the LDPE-Titania environment were further screened for their ability to form biofilm on LDPE films, salt aggregation test (SAT) and cell surface hydrophobicity. The potential bacterial strains were then identified as Pseudomonas aeruginosa (CA9), Burkholderia seminalis (CB12), and Stenotrophomonas pavanii (CC18) (GenBank accession number KR738718, KR738720 and KR738722, respectively) based on the 16S rRNA gene sequence homology. The strain CC18 showed highest biofilm, hydrophobicity and growth rate. The LDPE films of 3 × 3 cm were incubated with CC18 in mineral salt media (MSM) for 56 days. The viability tests of the isolates grown on LDPE surface were performed which also correlated with the protein density of biomass (R 2  = 0.98). LDPE films were characterized using SEM, TGA, XRD and FTIR before and after incubation. Biodegradation of LDPE was confirmed by an increase in the Keto Carbonyl, Ester Carbonyl and Vinyl Bond Index compared to control. The results conclusively demonstrated the potential of the LDPE-titania-starch blend for production of shopping bags which may easily be degraded in open environment after use. Highlights: Dye sensitized TNPs showed higher trajectory for photodegradation of LDPE films. Additional carbon source (i.e. glucose) negatively impacted the LDPE degradation. LDPE films modified with TNPs and starch showed higher degree of biodegradation. Dye sensitized TNPs created robust and easy colonizing sites on LDPE for CC18. Two step photo-biodegradation showed its potential for LDPE degradation in real environment.